BALB/3T3 cells infected by the ts3 mutant of polyoma virus fail to accumulate virus-specific early RNA at the nonpermissive temperature. - Cogen, B (1977)
We measured the accumulation of virus-specific early RNA in BALB/3T3 cells infected by the ts3 mutant of polyoma virus by annealing cytoplasmic RNA from infected cells to purified, radiolabeled, "early" strand of polyoma DNA. Cells infected by the ts3 mutant fail to accumulate virus-specific early RNA at the nonpermissive temperature.